Comparison of Computational and Previous Experimental Studies on Naphthyl Pyridyl Pyrazole (NPP) - Dakhil , Othman O.; Elmhdwi , Maraia F.; Elarfi , Mohamed J.; Al-Difar, Hussniyia A. (Scientific Journal of University of Benghazi, 2022)
The naphthyl pyridyl pyrazole (NPP) was the subject of a theoretical inquiry. The data determined through the calculations were supported by experimental results from 1HNMR and X-Ray techniques. Geometrical parameters and optimized energies for the NPP molecule were determined via density functional theory (DFT) at the B3LYP 6-311++G (d, p) level of theory. The vibrational spectra were obtained and the fundamental vibrations were assigned. 1HNMR chemical shifts were recorded by using the gauge-invariant atomic orbital (GIAO) method. Further, electronic properties such as HOMO and LUMO energies were determined via time-dependent density functional theory (TD-DFT). The results of the calculations were found to be comparable to the experimental results obtained.